Advanced Science and Technology Letters 2013
DOI: 10.14257/astl.2013.43.17
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Service Scheduling in Mobile P2P-based Video-on-Demand Streaming

Abstract: We propose an efficient multimedia service for mobile P2P network policy with the service patterns which mobile join and mobile node resource utilizations. And improves the cache utilization of user requests and reduces the starvation problem of nodes exit from the network. We test the performance of mobile P2P services with cache hit rate and fault with similar techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The previous study suggested a strategy of mobile P2P transmission for effective mobile service in the mobile P2P network environment, and a priority caching strategy for it [4]. This paper used the concepts of BO (bandwidth-ordered) tree, TO (time-ordered) tree, and RO (relay-join) tree so as to enhance transmission efficiency when new nodes join.…”
Section: Rdt(remaining Download Time) Systemmentioning
confidence: 99%
“…The previous study suggested a strategy of mobile P2P transmission for effective mobile service in the mobile P2P network environment, and a priority caching strategy for it [4]. This paper used the concepts of BO (bandwidth-ordered) tree, TO (time-ordered) tree, and RO (relay-join) tree so as to enhance transmission efficiency when new nodes join.…”
Section: Rdt(remaining Download Time) Systemmentioning
confidence: 99%